COMBINATION OF Azospirillum brasilense AND Bradyrhizobium japonicum IN THE PROMOTION OF INITIAL CORN GROWTH - Pereira, Gabriel Monteiro Aguiar; Menezes, Renato de Carvalho; Cunha, Marcos Gomes da; Carrer Filho, Renato (REVISTA DE AGRICULTURA NEOTROPICAL, 2021)
Biological formulations used as inoculants are increasingly present in grasses, especially in corn. Positive results in promoting plant growth, with different associations with diazotrophic bacteria, show these capacities of interaction to act as plant growth regulators, making it a promising alternative with a low environmental impact. Thus, this study aimed to evaluate the efficiency of inoculation and co-inoculation of nodulating and non-nodulating diazotrophic bacteria as promoters of initial growth in corn plants. Therefore, the bacteria Azospirillum brasilense (UFG21 strain), Bradyrhizobium japonicum (commercial product), and their co-inoculation were used in seed treatment. The evaluations consisted of growth measuring of the root system and shoot and evaluating leaf chlorophyll concentration. The results showed a beneficial interaction between the bacteria and the corn plant, with an increase in the root system and chlorophyll content, compared to the control treatment.